Stalking risks to celebrities and public figures. (25th April 2018) - Wilson, Simon; Dempsey, Charles; Farnham, Frank; Manze, Tony; Taylor, Alice
SUMMARY: Prominent figures are frequently subjected to unwanted and intrusive attentions. Such stalking behaviour is often driven by psychotic illness, angrily blaming the public figure for delusional persecution (resentful motivation), or based on erotomanic delusions (intimacy seeking motivation), for example. This behaviour can cause psychological harm to both perpetrator and victim, and is unlawful. In the rare instances where a public figure has been attacked, the perpetrator has usually had a history of such stalking behaviour and of severe mental illness. For these reasons, early identification and diversion into appropriate care and treatment will be for the benefit of both parties and will prevent more serious violence in a minority of cases. The importance of the provision of education to improve both reporting rates by victims and an appropriate response from the criminal justice system is highlighted. A multi-agency approach involving the criminal justice system and mental health services is the most effective means of achieving these aims. DECLARATION OF INTEREST: None. LEARNING OBJECTIVES: Learn that severe mental illness, particularly psychosis, is often an important driver of stalking behaviour Learn that delusional disorder is a treatable mental illness Appreciate that prevention rather than prediction is the approach to managing the risks of high-harm low-probability outcomes.